MINDFULNESS & MENTAL STRAIN AMONG ORGANIZATIONAL EMPLOYEES DURING PANDEMIC COVID-19 - Dr. Astha Bhanot, Dr. Naila Iqbal (Chelonian Research Foundation, 2023)
Over the last seven months, the COVID-19 virus has been spreading to all continents severely, which infects people in various nations around the world. The business, economy, and society are being affected due to the spreading of the virus. Because of virus spread, the government announced full lockdown and partial lockdown to all states. Due to lockdown and virus spread, there is a mental strain and mindfulness among employees. Stress is a significant problem since it can adversely affect the positive outcomes of work. The main objective of the present study was to examine the connections among mental health, particularly psychological distress and depression among managers. Additionally, the prospective moderating impact on the mindfulness about those interactions has been examined. This analysis employed a cross-sectional design to determine the three variables of interest (mental health (psychological distress, and depression), wellbeing, and mindfulness) across a survey. A sample of 180 managers has taken part. The results indicate that levels of mindfulness can protect the impacts that mental stress has on employee strength. The results also showed that COVID-19 related psychological distress is adversely associated with psychological distress and depression. Generally, those results offer initial research for mindfulness-based work interventions designed to improve worker flexibility among managers.